2017
DOI: 10.1007/s11829-017-9540-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of resistance to the bean weevil Acanthoscelides obtectus Say, 1831 (Coleoptera: Bruchidae) in common bean genotypes

Abstract: The bean weevil Acanthoscelides obtectus (Say, 1831) (Coleoptera: Bruchidae) is one of the most serious pests of stored beans worldwide because of the damage it causes to grains within warehouses. The use of resistant genotypes may offer a control strategy for this pest. In the current study, we screened common bean genotypes of Andean American and Mesoamerican origin in laboratory and greenhouse bioassays to select the most promising beans for resistance to the bean weevil. In the laboratory, we evaluated num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Bragantia, Campinas, 83, e20230173, 2024 Baldin et al (2017) used the same method and reported that genotypes Arcelin 1, Arcelin 2, Arcelin 1S, Arcelin 5S, and Arcelin 3S showed antibiosis resistance against A. obtectus, corroborating with the results of the present study. Conversely, in the present study genotype Arcelin 3 was grouped with genotypes with the highest oviposition, the largest number of emerged insects, and the highest larval viability (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Bragantia, Campinas, 83, e20230173, 2024 Baldin et al (2017) used the same method and reported that genotypes Arcelin 1, Arcelin 2, Arcelin 1S, Arcelin 5S, and Arcelin 3S showed antibiosis resistance against A. obtectus, corroborating with the results of the present study. Conversely, in the present study genotype Arcelin 3 was grouped with genotypes with the highest oviposition, the largest number of emerged insects, and the highest larval viability (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Arcelin is a protein toxic to several insects, including A. obtectus and Zabrotes subfasciatus (Mazzonetto and Vendramim 2002, Baldin and Pereira 2010, Baldin et al 2017, Tigist et al 2021. Currently, eight variants of arcelin have been identified in wild beans with different resistance levels to bruchids (Osborn et al 1986, Lioi and Bollini 1989, Cardona et al 1990, Santino et al 1991, Acosta-Gallegos et al 1998, Zaugg et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This cosmopolitan insect pest has also been reported as the most important pest of stored beans in Asia (Thakur, 2012), America (Quentin et al, 1991;Silva andCosta, 2016 andBaldin et al, 2017), Africa (Rugumamu, 2014), Europa (Rugumamu, 2014) and Oceania (Daglish et al, 1993). In fact, larvae of A. obtectus enter the common bean seeds from the first instar stage and consume the reserves contained in the cotyledons which causes great losses (up to 30%) (Baldin et al, 2017). Infestation of stored common beans by the bean weevil gives a characteristic pungent odour, making them unfit for consumption and reducing their market value (Paul et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The wild bean germplasms G12952 (ARC-4), G12949 (ARC-4) [ 32 ] and QUES (ARC-8) [ 40 ] are resistant to both A. obtectus and Z. subfasciatus . Baldin et al [ 41 ] screened 18 common bean genotypes of Andean American and Mesoamerican origin, and the common bean genotypes Arc.1, Arc.2, Arc.1S, Arc.3S, and Arc.5S were identified as resistant to A. obtectus . Some Bulgarian common bean genotypes and commonly grown Turkish bean genotypes were resistant against A. obtectus [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%